Genetic recombinants in Trichoderma pseudokoningii (Rifai) without typical parasexuality - Bagagli, E. [UNESP]; Furlaneto, M. C. [UNESP]; Pizzirani-Kleiner, A. [UNESP]; Azevedo, J. L. [UNESP] (Canadian Science Publishing, 1995)
Heterokaryons were obtained by hyphal anastomosis in Trichoderma pseudokoningii using strains with morphologic and double auxotrophic genetic markers. Stable haploid and unstable hyperhaploid recombinants were detected in monosporic colonies derived from heterokaryons and selected in appropriate media or by an enrichment filtration technique. Diploids were not observed and the recombinant frequencies were higher than those found in fungi with a typical parasexual cycle. The mechanism of recombinant emergence may involve a transient diploid formation followed by chromosomal losses at the hyphal stages, resulting in haploid and hyperhaploid recombinants. The possibility of intrachromosomal rearrangement with the involvement of cytoplasmatic DNA as a heterokaryotic transformation system cannot be excluded.
Keywords: Evolution; Parasexual process; Transformation; Trichoderma pseudokoningii